100 years of warfare from the First World War to the present day - Brewer, Paul (Andre Deutsch, 2015)
Presented in a dramatic newspaper style and covering all major battles, from the First World War to the Global War on Terror, this book is packed with information on important developments as well as details about the personalities who influenced the outcomes of wars across the world. It allows the reader to experience warfare as it was lived.